2022
DOI: 10.1111/1365-2656.13813
|View full text |Cite
|
Sign up to set email alerts
|

Extending the gleaner–opportunist trade‐off

Abstract: 1. Species exhibit various trade-offs that can result in stable coexistence of competitors. The gleaner-opportunist trade-off to fluctuations in resource abundance is one of the most intuitive, yet also misunderstood, coexistence-promoting tradeoffs. Here, we review its history as an ecological concept, discuss extensions to the classical theory and outline opportunities to advance its understanding.2. The mechanism of coexistence between species that grow relatively faster than their competitors in a low-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…We took a novel approach to evaluate the potential origin of this type of trade-off through evolutionary diversification of the traits themselves by using phylogenetic comparative methods to control for the evolutionary history of our focal species. As we did not find a gleaner-opportunist trade-off between photosynthetic traits our work supports the view that this trade-off may not be as widespread as previously assumed (Litchman et al, 2007; Isanta-Navarro et al, 2022; Yamamichi & Letten, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We took a novel approach to evaluate the potential origin of this type of trade-off through evolutionary diversification of the traits themselves by using phylogenetic comparative methods to control for the evolutionary history of our focal species. As we did not find a gleaner-opportunist trade-off between photosynthetic traits our work supports the view that this trade-off may not be as widespread as previously assumed (Litchman et al, 2007; Isanta-Navarro et al, 2022; Yamamichi & Letten, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Gleaner-opportunist trade-offs are believed to be important in the maintenance of diversity in ecological communities (Litchman et al, 2007; Yamamichi & Letten, 2022). The underlying assumption is that this trade-off allows for the coexistence of multiple species when they are competing for a variable resource.…”
Section: Introductionmentioning
confidence: 99%
“…For a replicating rather than a spontaneously generated resource, this allows the possibility of stable limit cycles. When different non-linear function responses (for example, when 𝜏 1 ≠ 𝜏 2 ) result in a trade-off between fitness in low-resource environments (gleaners) and high-resource environments (opportunists), resource oscillations may contribute to species coexistence (Armstrong andMcGehee 1980, Yamamichi andLetten 2022). The interplay of this effect with interference competition is beyond the scope of our study.…”
Section: Caveats Future Directions and Conclusionmentioning
confidence: 97%
“…More recently, an increasing number of empirical studies have demonstrated that temporally fluctuating selection/environments are important in maintaining both genetic variation (Bergland et al, 2014; Machado et al, 2021; Rudman et al, 2022; Yi & Dean, 2013) and species diversity (Angert et al, 2009; Ellner et al, 2019; Hallett et al, 2019; Letten et al, 2018; Sommer, 1985; Zepeda & Martorell, 2019). Although the topic itself has a long history in ecology (reviewed in Barabás et al, 2018; Chesson, 2000b; Ellner et al, 2019; Stump & Vasseur, 2023; Yamamichi & Letten, 2022)and evolutionary biology (reviewed in Felsenstein, 1976; Frank, 2011; Gillespie, 1991; Hedrick, 1986; Hedrick, 2006; Hedrick et al, 1976; Johnson et al, 2023: see also Figure 1 and Figure S1), the recent accumulation of empirical evidence has coincided with renewed theoretical interest into the role of temporally fluctuating environments in maintaining genetic variation (Bertram & Masel, 2019b; Dean, 2018; Dean et al, 2017; Gulisija et al, 2016; Kim, 2023; Novak & Barton, 2017; Park & Kim, 2019; Schreiber, 2020; Svardal et al, 2015; Wittmann et al, 2017, 2023; Yamamichi et al, 2019; Yamamichi & Hoso, 2017) and species diversity (Barabás et al, 2018; Chesson, 2018; Ellner et al, 2019; Fung et al, 2022; Johnson & Hastings, 2022a, 2022b; Meyer et al, 2022; Pande et al, 2020; Schreiber, 2021, 2022; Schreiber et al, 2019).…”
Section: Introductionmentioning
confidence: 99%